Middle East experience from the Asia And Latin America Fracture Observational Study (ALAFOS): Baseline characteristics of postmenopausal women with osteoporosis using teriparatide. Issue 8 (August 2020) - Elsalmawy, Abdul Aziz; Al-Ali, Nadia S.; Yaghi, Yasser; Assaggaf, Hussein; Maalouf, Ghassan; Sadat-Ali, Mir; Zaher, Essam; Saghieh, Said; Mahmoud, Ahmed; Taher, Mohamed
Objective: We aimed to describe the baseline clinical characteristics and fracture history of patients taking teriparatide in routine clinical practice in the Middle East (ME) subregional cohort of the Asia and Latin America Fracture Observational Study (ALAFOS). Methods: Herein, we report baseline clinical characteristics of patients who were prescribed teriparatide (20 µg/day, subcutaneous injection) in four participant ME countries (Saudi Arabia, United Arab Emirates, Kuwait, and Lebanon). Results: The ME cohort included 707 patients mean (SD) age 69.3 (11.6) years. Mean (SD) bone mineral density (BMD) T-scores at baseline were −3.13 (1.28) for lumbar spine, −2.88 (0.94) for total hip, and −2.65 (1.02) for femoral neck. Osteoporotic fractures after age 40 years were reported in 45.8% (vertebral fracture 14.4%, hip fracture 18.4%) and comorbidities in 57.4% of patients. Before starting teriparatide, 19.9% of patients took other osteoporosis medications. The median (Q1; Q3) EuroQoL 5-Dimension 5-Level visual analog scale score for perceived overall health status was 70 (50; 80). Mean (SD) worst back pain in the previous 24 hours was 4.0 (3.2) using a 10-point numeric rating scale. Conclusion: This analysis indicated that in ME countries, teriparatide is usually prescribed to patients with low BMD and high comorbidities, with prior fractures.